2001
DOI: 10.1093/humupd/7.6.591
|View full text |Cite
|
Sign up to set email alerts
|

PGD in female carriers of balanced Robertsonian and reciprocal translocations by first polar body analysis

Abstract: Preimplantation genetic diagnosis (PGD) using the first polar body (1PB) is a modality of PGD that can be used when the woman is the carrier of a genetic disease or of a balanced chromosomal reorganization. PGD using 1PB biopsy in carriers of balanced chromosome reorganizations has not become generalized. Here, we describe our experience based on the analysis of unfertilized or fresh, non-inseminated control oocytes, by fixing separately the 1PB and the corresponding oocyte, and on the study of six clinical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 26 publications
0
27
0
2
Order By: Relevance
“…A review on maternally derived reciprocal translocations (Durban et al 2001) showed that 56% of the oocytes diagnosed through first polar body (1PB) were unbalanced. On the other hand, Findikli (2003) also found a high percentage (69.2%) of unbalanced oocytes in female reciprocal translocation carriers.…”
Section: As In Reciprocal Translocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review on maternally derived reciprocal translocations (Durban et al 2001) showed that 56% of the oocytes diagnosed through first polar body (1PB) were unbalanced. On the other hand, Findikli (2003) also found a high percentage (69.2%) of unbalanced oocytes in female reciprocal translocation carriers.…”
Section: As In Reciprocal Translocationsmentioning
confidence: 99%
“…Consequently, this method can be considered as not applicable for the detection of the unbalanced status of the translocations described. (d) PGD analysing of polar bodies (PBs), which can be used when the female is the carrier of a genetic disease or of a balanced chromosomal rearrangement (Durban et al 2001, Verlinsky et al 2004 or for aneuploidy screening (AS) in cases of advanced maternal age or in vitro fertilization (IVF) failures , Verlinsky et al 2004. This modality of PGD can be used alone or in combination with blastomere biopsy (Magli et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fixation of 1PBs was made using a modification of Durban et al, 24,32 which helps to reduce chromosome losses to a minimum and practically eliminates artefactual errors. Oocytes were fixed using a modification of a described method.…”
Section: European Journal Of Human Geneticsmentioning
confidence: 99%
“…23 By analysing 1PBs, errors related to embryo mosaicism can be avoided, there is time to perform up to three rounds of FISH and, if problems have occurred during the process, a blastomere can be biopsied and analysed on time before transfer. Recently, a preimplantation genetic diagnosis using IPB (PB (PGDÀ1PB)) protocol in which ICSI was performed before 1PB biopsy was applied, 24 and the fertilisation rate achieved was comparable to the one obtained in IVF-ICSI cycles without PGD. Moreover, different types of FISH probes, (CEP), centromeric locus specific (LSI) and whole chromosome painting (WCP) can be used because the 1PB is in metaphase, and, when fixed, chromosome spreads are obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation